2020
DOI: 10.3390/nu12092618
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Nypa fruticans Wurmb by Suppressing TRPV1 Following Sciatic Nerve Crush Injury in a Rat

Abstract: Peripheral nerve injury can result in severe functional impairment and decreased quality of life due to loss of sensory and motor function. Nypa fruticans wurmb (NF) has been used in diverse folk remedies in East Asia. We have previously shown that Nypa fruticans wurmb extract has antinociceptive and anti-inflammatory effects by suppressing TRPV1 in the sciatic nerve injury. The present study investigated the effects of NF on the control of TRPV1 in relation to neuroprotective effects of a sciatic nerve crush … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Fortunately, pharmacological treatments have also been shown to promote nerve regeneration. Therefore, cost‐effective and easy‐to‐use drugs, especially natural drugs (Kang et al, 2020; Ma et al, 2013), are actively being explored.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, pharmacological treatments have also been shown to promote nerve regeneration. Therefore, cost‐effective and easy‐to‐use drugs, especially natural drugs (Kang et al, 2020; Ma et al, 2013), are actively being explored.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, flavonoids and polyphenols present in plants reportedly inhibit melanogenesis (17)(18)(19)(20). Studies have indicated that NF has anti-nociceptive, neuroprotective, and anti-inflammatory properties (21,22). Therefore,…”
Section: Introductionmentioning
confidence: 99%
“…In addition, flavonoids and polyphenols present in plants reportedly inhibit melanogenesis ( 17-20 ). Studies have indicated that NF has anti-nociceptive, neuroprotective, and anti-inflammatory properties ( 21 , 22 ). Therefore, we investigated the inhibitory effect of the ethyl acetate fraction of N. fruticans (ENF) on melanogenesis and cell signaling pathways via AKT/mammalian target of rapamycin (mTOR)/CREB and mitogen-activated protein kinase (MAPK).…”
Section: Introductionmentioning
confidence: 99%